Determining the level of miRNA 133a-5p and Mid Regional pro-Adrenomedullin in Patients with Stable Angina Pectoris - Aseel Ghassan Daoud; Ahmed Yousif Hasan; Wassan Abdul Kareem Abbas (Iraqi Journal of Pharmaceutical Sciences, 2025)
Chronic stable angina pectoris (CSAP) is a prevalent heart disease which can be defined as a symptom or a clinical syndrome of stable coronary artery disease (CAD). CAD is usually caused by the presence of atherosclerotic plaques or blood clot within coronary arteries that may lead to ischemia. miRNA 133a is mainly expressed in the muscle and it has a role in apoptosis, angiogenesis, hypertrophy, atherosclerosis and ischemia. MR-proADM is of endothelial origin and produced by different sites in the body mainly by the heart, kidneys, lungs and adrenal medulla. MR-proADM plasma level is thought to be predictive of CAD. The aim of the current study was to detect the serum levels of microRNA 133a-5p and MR-proADM in a sample of Iraqi patients with chronic stable angina and obstructive CAD with normal LV ejection fraction so that to investigate whether these biomarkers can be used to diagnose those patients. In this case-control study, fasting venous blood samples were collected from 90 male and female subjects (40-76 years old) who were presented to the outpatient clinic as having chest pain. An electrocardiography, echocardiography and conventional coronary angiography were applied by the cardiologist for all the participants. Routine biochemical tests and patients questionnaire were also applied. Left ventricular ejection fraction was detected using the biplane M mode method. Accordingly, the patients who showed evidence of atherosclerotic plaque and CAD on the angiography were classified as angina patients (n=60) and those who showed no evidence of coronary obstruction and ischemia on the angiography (normal angiography) were classified as being a control group (n=30). The fold of gene expression of miRNA 133a-5p in serum and serum levels of MR-proADM, fasting blood glucose (FBG), urea, creatinine, TGs, total cholesterol, LDL-C, HDL-C and VLDL-C were measured. Results: the fold of miRNA 133a-5p gene expression in serum and the serum levels of MR-proADM were significantly higher in patients (P≤ 0.01) and ROC curve showed that miRNA 133a-5p had 98% sensitivity and 47% specificity with AUC=0.8, whereas, MR-proADM had 100% sensitivity and 100% specificity with AUC=1.0. So, it can be concluded that MR-proADM could be used as an independent biomarker for the diagnosis of stable angina patients with normal LV ejection fraction, whereas microRNA 133a-5p is better to be used in combination with other biomarkers to give more accurate diagnosis.